Implanty ślimakowe – etyka a wybór - Tomaszewski , Piotr (Kultura-Społeczeństwo-Edukacja, 2018)
Tomaszewski Piotr, Implanty ślimakowe – etyka a wybór [Cochlear implants – ethics and choices]. „Kultura – Społeczeństwo – Edukacja” nr 2(14) 2018, Poznań 2018, pp. 155–181, Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2018.14.13. This study discusses the ethical issue of the development of hearing technology in the form of cochlear implants that are used by an ever-growing number of deaf and hard of hearing people. The development of this kind of technology has progressed so quickly all over the world, including Poland, that the deafness paradigms have drastically changed. This may affect, to a greater or lesser degree, not only the implementation of early support programmes, but also the image of the Deaf communities using their respective sign languages on a daily basis. It is therefore necessary to create an eclectic model of education for deaf and hard of hearing people which would allow for the ethical option to integrate the conflicting approaches on the proper procedure for deciding on the language (spoken or signed) and the culture (the hearing or the Deaf one) for the development of deaf and hard of hearing students with cochlear implants or hearing aids.